Consumer Empowerment: Safeguarding Consumer Rights Through BPSK’s Arbitration Post the Constitutional Court Decision: Pemberdayaan Konsumen: Melindungi Hak Konsumen Melalui Proses Arbitrase di BPSK Pasca Putusan Mahkamah Konstitusi - Yulistyaputri, Rizkisyabana; Lestarini, Ratih (Jurnal Konstitusi, 2023)
The arbitration decision by BPSK, can be filed with objections in accordance with Law 8/1999 and annulment under Law 30/1999. These two actions raise questions related to the arbitration process to resolve consumer disputes, consumer protection, and the impact of the Constitutional Court’s decision on the annulment of arbitration awards. This is because both actions are contrary to the final and binding nature of the arbitration award. Through the doctrinal research method, it was found that three years since the Constitutional Court’s Decision, there has been an increase in decisions related to the annulment of arbitration awards and objections to BPSK decisions. The Constitutional Court Decision has two contrary impacts. It makes easier for the aggrieved party in the process of resolving consumer disputes through arbitration to file for annulment or objection. Meanwhile, it also makes the process of consumer protection through arbitration lose its final and binding force.